Green synthesis of silver nanoparticles using Morus nigra leave extract and evaluation their antifungal potency on phytopathogenic fungi - Rania A. Hafez, Mosaad A. Abdel-Wahhab, Ahmed F. Sehab, Al-Zahraa A. Karam El-Din (Journal of Applied Pharmaceutical Science, 2017)
This study aimed to isolate and identify the fungi associated with white and yellow corn grain and peanuts seeds samples collected from different distracts at Cairo, to use Morus nigra leaves extract for the green synthesis of silver nanoparticles (AgNPs) and to evaluate the antifungal potency and anti-aflatoxin production of the synthesized AgNPs. White and yellow corn and peanut seeds samples were collected from 4 different districts of Cairo, mycoflora were isolated on Potato dextrose agar (PDA), Nash and Coon’s media. The results revealed the isolation of sixteen fungal species belonging to 7 genera were recovered and identified during this study. The produced AgNPs showed Uv/Vis absorbance at 425 nm and particles sizes ranged from 4 to 8 nm. Both AgNPs and the plant extract showed a strong antifungal activity against P. carryophylum; F. verticillioides; A. flavus; A. terreus and F. oxysporum using different techniques. Moreover, AgNPs was more effective than the plant extract against the tested fungi and anti-aflatoxin production by A. parasiticus. It could be concluded that the Morus nigra leaves extract can be used for the syntheses of AgNPs and also as antifungal of plant disease. Thus, Morus nigra and AgNPs could be used as effective, safe and ecofriendly antifungals to prevent fungal growth and subsequent aflatoxins production.
Keywords: Morus nigra, antifungal potential, nanosilver, antimycotoxin activity, aflatoxins.